Obravnava bolnika z delirijem - Korošec Jagodič, Helena (Zdravniški vestnik, 2009)
Background Delirium is defined as an impairment of counsciousness and cognitive functions and is a common cause of disturbed behaviour in many patients with different somatic diseases and mental disorders. Most at risk are elderly, postoperative patients, critically ill patients and those with cancer in advanced stages. In psychiatric intensive care units patients with alcohol and sedative withdrawal related delirium are more often treated. Although delirium is a negative prognostic indicator leading to higher morbidity and mortality of patients, it often goes undetected and poorly managed. Conclusions Most recommendations for management of delirium are basedon the nonpharmacological supportive care and prevention of delirium. It is also necessary to identify and treat the underlying causes. Antipsychotics are the mainstay of symptomatic pharmacological treatment and have been shown to be effective in treating symptoms of both hyperactive and hypoactive delirium. Although efficacy rates between typical and atypical antipsychotic agents are similar, the later are associated with fewer extrapyramidal side effects. Benzodiazepines are usually preferred for withdrawal delirium or as an alternative or adjuvant to antipsychotics when these are ineffective or cause unacceptable side effects.
Keywords: Acetilholin; Acetylcholine; Alcohol Withdrawal Delirium; Antipsihotiki; Antipsychotic Agents; Benzodiazepines; Benzodiazepini; Delirij; Delirium; Delirium tremens; Diagnosis; diagnostika; Dopamin; Dopamine; Intensive Care Units; Intenzivna oskrba, enote; Physiopathology; Therapy; zdravljenje; zmedenost